Relevance of tributary inflows for driving molecular composition of dissolved organic matter (DOM) in a regulated river system. (15th June 2023) - Acharya, Suman; Holland, Aleicia; Rees, Gavin; Brooks, Andrew; Coleman, Daniel; Hepplewhite, Chris; Mika, Sarah; Bond, Nick; Silvester, Ewen
HIghlights: Influence of unregulated tributary on DOM in a regulated river was explored. DOC, DON and DOP concentrations varied between regulated and unregulated river. Tributary characterised by higher amounts of high MW, aromatic, terrestrial DOM. Regulated river contained lower DOM concentrations and more autochthonous DOM. Tributary inflows during storm pulses restore DOM dynamics in the regulated river. Abstract: River regulation by dams can alter flow regimes and organic matter dynamics, but less is known about how unregulated tributaries regulate organic matter composition and processing in the regulated river below the confluence. This study reports on water chemistry, especially dissolved organic matter (DOM) concentration and composition (dissolved organic carbon (DOC), organic nitrogen (DON), organic phosphorus (DOP) and combined amino acids (DCAA)) along the regulated Tumut and unregulated Goobarragandra (tributary) rivers under different flow conditions (base flow vs storm event) in south-east Australia. The tributary was significantly different from regulated and downstream sites during base flow conditions with higher temperature, pH, buffering capacity, DOC and nutrient concentrations (DON, DOP, DCAA). DOM characterisation by spectrometry and size exclusion chromatography revealed that the tributary contained a higher proportion of terrestrially derived humic-like and fulvic-like DOM. In contrast, regulated and downstream sites contained higher proportion of microbially derived DOM such as low molecular weight neutrals and protein-like components. Storm pulses of tributary flows into the regulated system, influenced both concentration and composition of DOM at the downstream site, which more strongly resembled the tributary site than the regulated site during the storm event. Additionally, we found that the tributary supplied fresh DOM, including small organic molecules to the regulated system during storm events. The presence of these different types of labile DOM can increase primary productivity and ecological functioning within regulated river reaches downstream of tributary junctions. This has important implications for the protection of unregulated tributary inflows within regulated river basins. Graphical Abstracts: Image, graphical abstract